ANALYSIS OF MATERNAL HEALTH PROGRAMS IN KWALA BEKALA, MEDAN JOHOR: THEIR IMPACT ON FUTURE GENERATIONS’ HEALTH YEAR 2026 - Simanullang, Ester; Imran Saputra Surbakti; Nur Azizah; Tri Hidayah Akma Maha; Himawari Kirina Petranela Sriyani; Irwanta Ginting (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Maternal health is a critical component of public health, as the well-being of mothers directly influences the survival and development of future generations. Pregnancy is a vulnerable period in which women require adequate healthcare services, nutritional support, and community-based interventions to ensure safe delivery and healthy outcomes for both mother and child. Globally, maternal health programs have been established to reduce maternal and infant mortality rates, yet challenges remain in ensuring equitable access and effective implementation at the local level. In Indonesia, maternal health continues to be a priority within national health strategies, particularly in urban and semi-urban communities where disparities in healthcare access still exist. Kelurahan Kwala Bekala, located in Medan Johor, represents a community where maternal health programs play a vital role in shaping the quality of life and future health of its residents. Understanding how these programs are implemented, and analyzing their impact on the health of future generations, is essential for strengthening community-based health initiatives. This study seeks to analyze maternal health programs in Kelurahan Kwala Bekala, Medan Johor, with a focus on their effectiveness, challenges, and long-term implications for the health of future generations. By examining local practices and outcomes, the research aims to provide insights that can contribute to policy development and improved maternal health services at the community level.